PENGUATAN KOMPETENSI PENGETAHUAN SISWA MELALUI EDUKASI INTERAKTIF BERBASIS TEKNOLOGI DALAM PROGRAM PENGABDIAN KEPADA MASYARAKAT DI SD NEGERI KUTA PASI - jolheri (Jurnal Pengabdian Pemersatu Bangsa, 2025)
Community service programs represent one of the implementations of the university’s tridharma which aims to contribute to improving the quality of education in society. This activity was conducted at SD Negeri Kuta Pasi with the objective of strengthening students' knowledge competencies through technology-based interactive education. The implementation method consisted of preparation, implementation, and evaluation stages. During the implementation phase, the service team delivered learning materials through interactive lectures, discussions, demonstrations, and the use of digital learning media such as visual presentations and educational videos. The activity involved elementary school students who actively participated in the learning process. The results indicated that the use of technology-based learning media was able to increase students' learning interest, participation, and understanding of the material presented. Furthermore, interactive learning approaches provided more engaging and effective learning experiences for students. Therefore, this community service activity contributed positively to improving the quality of the learning process in the elementary school environment.